Fluctuations in Seminal Quality throughout the Year: How do Temperature, Humidity and Atmospheric Pressure Impact on Human Sperm Quality? - Nicolás David Ramírez; Andrea Tissera; Rosa Molina; Jose Olmedo; Héctor Guillermo Molina; Arnaldo Mangeaud; Ana Carolina Martini (Journal of Human Reproductive Sciences)
Background: Most studies evaluating the possible seasonal variation of semen quality have considered temperature as the only causal factor. Aims: To assess possible seasonality in sperm quality and associations between semen parameters and several meteorological variables (temperature, humidity, apparent temperature and atmospheric pressure) in a large cohort of andrological patients. Settings and Design: This was a retrospective, cross-sectional and correlational/descriptive study. Materials and Methods: Patients (n: 15665) were categorised into four groups (summer, winter, spring and autumn) according to the date of assistance at the fertility centre. Daily values of temperature, apparent temperature, humidity and atmospheric pressure were provided by the National Weather System and were calculated as the average of the 74 days previous to semen collection (spermatogenic cycle). Statistical Analysis Used: As appropriate, the results were analysed by analysis of variance/Kruskal–Wallis, Chi-square test, t-test/Mann–Whitney, forward conditional regression model and Spearman/Pearson’s correlations. Results: We detected seasonality effects on sperm count, total sperm count and total motile sperm count, with the highest values in winter and the lowest in summer. Correlation analysis showed that temperature, apparent temperature and humidity negatively correlated with semen parameters, being humidity the most powerful predictive meteorological variable. Conclusion: Sperm quality is influenced by seasons; increased environmental temperature and humidity negatively affect semen quality.